The influence of the anisotropic temperature of the electron gas on energy losses of a charged particle in a plasma - Khelemelia, O.V.; Kholodov, R.I. (Вопросы атомной науки и техники, 2015)
Analytical expressions of real and imaginary parts of the dielectric susceptibility of the electron gas with an anisotropic velocity distribution are obtained within the quantum-field method. Energy losses of the projectile charged particle in an electron gas are calculated in the cases of an isotropic velocity distribution of electron gas and of the longitudinal motion in an medium with anisotropic temperature. The numerical results are confirmed by analytical expressions in the low temperatures approximation. В рамках квантово-полевого метода получено аналитическое выражение для реальной и мнимой частей диэлектрической восприимчивости электронного газа с анизотропным распределением. Подсчитаны энергетические потери массивной заряженной частицы в электронном газе в случае изотропного распределения по скоростям и в случае движения налетающей частицы в направлении анизотропии. Результаты численного счета энергетических потерь подтверждаются аналитическими расчетами в приближении малых температур. У рамках квантово-польового методу отримано аналітичний вираз для реальної та уявної частин діелектричної сприйнятливості електронного газу з анізотропним розподілом за швидкостями. Підраховано енергетичні втрати масивної зарядженої частинки в електронному газі у випадку ізотропного розподілу за швидкостями та у випадку руху налітаючої частинки в напрямку анізотропії. Результати чисельного обчислення енергетичних втрат підтверджуються аналітичними розрахунками в наближенні малих температур.